2017
DOI: 10.1002/chem.201605307
|View full text |Cite
|
Sign up to set email alerts
|

Anion–π Interactions in Flavoproteins Involve a Substantial Charge‐Transfer Component

Abstract: Anion-π interactions have been shown to stabilize flavoproteins and to regulate the redox potential of the flavin cofactor. They are commonly attributed to electrostatic forces. Herein we show that anion-flavin interactions can have a substantial charge-transfer component. Our conclusion emanates from a multi-approach theoretical analysis and is backed by previously reported observations of absorption bands, originating from charge transfer between oxidized flavin and proximate cysteine thiolate groups. This p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 36 publications
(62 reference statements)
1
16
0
Order By: Relevance
“…Finally, it is customary to reference, that London dispersion forces is a crucial component of intramolecular dihydrogen bonding C−H⋅⋅⋅H−C in addition to charge delocalization contribution . The importance of the latter term in other untypical anion‐π interactions has been also recognized . To further reference, an excellent review on homopolar dihydrogen contacts in hydrogen storage materials is available in Ref.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, it is customary to reference, that London dispersion forces is a crucial component of intramolecular dihydrogen bonding C−H⋅⋅⋅H−C in addition to charge delocalization contribution . The importance of the latter term in other untypical anion‐π interactions has been also recognized . To further reference, an excellent review on homopolar dihydrogen contacts in hydrogen storage materials is available in Ref.…”
Section: Resultsmentioning
confidence: 99%
“…The interaction energies computed using a triple‐zeta polarized Slater‐type basis set from the ADF library follow the same trends as the bond dissociation energies in Table . Analysis of the ZR‐EDA energy components unveils some general trends: 1) in all cationic complexes the orbital interaction is large, and for nonpolar graphane flakes it is the dominant energy component; and 2) among anionic systems, fluoride complexes benefit from the electrostatic term far more than their chloride and bromide counterparts, yet the orbital interaction is the main driving force for bond formation . ZR‐EDA reveals that the interplay between orbital interaction energy, electrostatics, and Pauli repulsion is responsible for the observed trends in the anion and cation affinities of G‐FF and G‐MeMe (see Supporting Information for description).…”
Section: Resultsmentioning
confidence: 94%
“…Among all noncovalent interactions related to aromatic rings, anion-π interactions received the most attention in the last few years. Due to their significant role in aforementioned supramolecular chemistry [4][5][6][7], crystal engineering [8][9][10][11] and structural biology [12][13][14][15], these interactions became a subject of great interest. Anion-π, also referred to as anion-quadrupole, interactions are theorized to form between aromatic groups and anions.…”
Section: Introductionmentioning
confidence: 99%
“…Using the systematic search of protein structures followed by ab initio calculations, Deyà and co-workers showed that anion-π interactions are to be expected in flavin-dependent enzymes [18]. Anion-π interactions have been shown to stabilize flavoproteins and to regulate the redox potential of the flavin cofactor [15]. In addition, Moore and co-workers examined high-resolution structures of proteins and nucleic acids for the presence of " 6 "-type anion-π contacts, where the anion is placed directly above the centre of the six-membered ring [12].…”
Section: Introductionmentioning
confidence: 99%